Mucinous cystadenoma of the appendix - Vudutha Srihari (Journal of Dr. NTR University of Health Sciences, 2015)
We present a case of 50-year-old man came with abdominal pain for 3 months who was investigated and found to be suffering from mucinous cystadenoma of the appendix for which who have done appendicectomy and ileotransverse anastomosis. Surgical specimen sent to pathology for histopathological examination revealed mucinous cystadenoma of the appendix.